Ethanol Dehydration in Fixed Bed Column Using Pellet Adsorbent From Natural Zeolite Lampung - Adisaputro, Jonathan Kristian; Ginting, Simparmin Br. (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2022)
This research is motivated by the reduced reserves of fossil fuels in Indonesia, so that fossil fuel substitutes are needed, one of which is ethanol. It's just that to make ethanol as a fuel substitute for fossil fuels, a 99% concentration is required, while the ethanol on the market only has a concentration of 96%. One of the processes that can be used to purify ethanol is the adsorption process. In this study, activation of Natural Zeolite Lampung (ZAL) was carried out to increase its adsorption ability to water contained in an ethanol-water solution. This zeolite modification process begins with ZAL pre-treatment, formation of ZAL in the form of pellets, then ZAL activation by calcination, the results of this modification are characterized through the FTIR, XRD, XRF, SEM, and BET mechanisms. ZAL has been successfully formed into pellets, this can be seen when ZAL is immersed and the ethanol-water solution is flowed, it does not change shape. The highest R2 value was obtained in the Adam Bohart equation model at a flow rate of 10 ml/minute with an R2 value of 0.9742 with the highest concentration achieved at a concentration of 98.797%.